Strategi Bersaing UMKM Toko Roti dan Kue di Kecamatan Bontang Utara Kota Bontang Selama Pandemi Covid-19 dan Pasca Pandemi Covid-19 - Muhammad Fachrun Fachrezi; Ana Noor Andriana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Toko Ria Rasa Cake & Bake, Toko Nanis Cake & Bakery, and Samabread are the local UMKM located in North Bontang District, Bontang City. The purpose of this research is to find out and determine the appropriate competitive strategy for the three UMKM. This type of research is qualitative. Sources of research data are key informants and supporting informants. Data collection techniques in research are interviews and observations. The analysis technique used is SWOT analysis (IFAS, EFAS, SWOT Analysis Diagram, and SWOT Matrix). The result and conclusion from this research is that the target to be achieved is to open branches or shops in other places to expand the market. The products that are sold vary widely, ranging from sweet to salty, and there is bread made from natural ingredients without chemical food ingredients. The price of each bread also varies, which can cover various economic groups. The three UMKM do not mind the existence of competitors with big brand names as long as these brands can compete healthily. Strategies to survive during the Covid-19 pandemic are almost the same as maximizing online sales on social media, carrying out safe packaging by spraying disinfectants, and shipping using your courier or courier from outside. The strategy resulting from mapping the SWOT matrix for the three UMKM is the SO strategy.